DIFFERENT LOCATIONS OF OROFACIAL PAIH AND US ASSOCIATION WITH AGE AND GENDER AT ISRA DENTAL COLLEGE, HYDERABAD - Salman Shafiquel , Aswad Ahmed2. Alvina Ali Shaikh3, Fahad Ahmed4,Rida Fatima Shah5,Laraib Iftikhar6, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2019)
Objective: To determine the different locations of orofacial pain and its association with age and gender among patients presented at lsra dental College, Hyderabad MaterialsandMethods: This observational study took place at Isra Dental College. Hyderabad. Study duration was 6 months from august 2018 January 2019. All the patients presented with agr morr than 12 years, orolâciai gaizt add either où gendcr was incJudccL Paôcnts wrzc Ïntcrvîc ted tegarTqg dcmogragbic ia€ozmaôcn inc1uding duration and location of the pain. All the data was recorded in self-made proforma. Results:Total 710 patients were studied: most common ege gmups were 31-40 years for 26.39 cases, followed by 41-50 years for 25.9& cases. females were 52.0& and males were 48.0&.Teeth pain was most commr›n in 78.6Re patents. followed by inside mouth pain in 12.19, face pain in 8.696 patients and headache in 0.7'Z• cases. Most ot the patients (63.8&) presented with acute pain. No significant variance was found in orofacial pain accord ng to age and gender; p-values were quite însignificant. CoimIu8ion: It was concluded thai mosi common pain Ination was tooth. Addjtionelly. no significant variance was seen in Age and gender in terms of orofacial pain matrons.